HOW COVID-19 AFFECTS LIBRARIES IN MONGOLIA - Ganbaatar, Tseren, Dr., Associate Professor; Otgondoo, Narantuya; Mashbat, Zolboo (Paradigma: Jurnal Kajian Budaya, 2023)
Globally, the COVID-19 pandemic has significantly impacted all spheres of the education industry, including libraries. The absence of emergency plans for unforeseen situations like COVID-19 disrupted regular operation and demanded the adoption of new operational protocols. The objectives of this paper are to examine the impact of COVID-19 on library operations, to identify the challenges encountered in libraries, to examine the changes in users’ service preference, and to reflect on the best practice for library operations in the future. To achieve these research objectives, both qualitative and quantitative research methods were employed. Surveys and interviews were conducted to understand changes in users’ service access, librarians’ daily work, and the library operations. Based on the findings, we reflect on how libraries should perform in the future for the best interests of their users.